1999
DOI: 10.1002/(sici)1522-2594(199907)42:1<6::aid-mrm2>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

?Silent? MRI with soft gradient pulses

Abstract: A method to reduce the acoustic noise generated by gradient systems in magnetic resonance imaging (MRI) is proposed based on the linear response theory. Since the acoustic frequency response function of typical gradient coils is low in the range below 200 Hz, the noise level can be significantly reduced by using gradient pulse sequences whose spectra are limited to this frequency range. Such ''soft,'' i.e., band-limited, pulse shapes can be designed using sinusoidal ramps individually adjusted to available del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
104
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 21 publications
(22 reference statements)
0
104
0
Order By: Relevance
“…For example, with Lorentz force balancing only a 10 dB reduction is achievable at 1.0 kHz. Recent new approaches attempt to solve the problem either by degrading rise time in gradient pulses (6) or by using vacuum technology (7).…”
mentioning
confidence: 99%
“…For example, with Lorentz force balancing only a 10 dB reduction is achievable at 1.0 kHz. Recent new approaches attempt to solve the problem either by degrading rise time in gradient pulses (6) or by using vacuum technology (7).…”
mentioning
confidence: 99%
“…13,23 An early attempt at a silent pulse technique was a sinusoidal waveform for gradient driving. 26 Although noise levels of 40 dB (A) (spin echo: SE or gradient echo: GE) and 60 dB (A) (rapid acquisition with relaxation enhancement: RARE) were achieved using a sinusoidal waveform, the special hardware requirements for this method limited its advantages. By development of silent pulse sequences was further initiated by the demand for functional neuroimaging.…”
Section: Discussionmentioning
confidence: 99%
“…7 These currents, in the presence of the strong static magnetic field of the MR imaging system, induce significant (Lorentz) forces that cause vibrations in the gradient coils, which, in turn, generate a compression wave in the air perceived as the scanner noise. [8][9][10] Previous methods used to ameliorate the high acoustic noise levels of clinical MR imaging include acoustic insulation of the scanner bore, resulting in reduced bore diameter and gradient waveform shaping/filtering 11,12 ; bandwidth limiting 13 ; and restricting gradient performance-each trading image quality and acquisition speed for only modest noise reduction. More recent studies have demonstrated that innovative pulse-sequence modifications can be applied to achieve substantial reductions of acoustic noise while maintaining image quality.…”
mentioning
confidence: 99%